Web-based Point of Sale (POS) information system at PT Sinergi Nusa Inovative using odoo (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2023)
The development of the world of technology continues to change all the time by following the needs of complex human work. One example of an information system that continues to grow to assist the needs of sales transactions is the Point of Sale (PoS). Point of Sale serves not only to process sales transactions, but also to assist the business processes of a business. This PoS information system was built using the prototyping method. Data collection techniques used are interviews, observations, and literature studies to analyze the needs of the PoS information system. The design of the POS information system uses the Unified Modeling Language (UML) to describe the processes that occur in the information system. The diagrams used are use case diagrams, activity diagrams, class diagrams, and sequence diagrams. Then also used Odoo to assist with system development. The programming language used is Python and XML, and on the database side, used Postgres SQL.